Current knowledge on Turkish tardigrades with a description of Milnesium beasleyi sp. nov. (Eutardigrada: Apochela: Milnesiidae, the granulatum group) - Kaczmarek, Łukasz; Jakubowska, Natalia; Michalczyk, Łukasz (Zootaxa, 2012)
In two moss samples collected from Turkey four tardigrade species, including a species new for science and a new recordfor the country, were found. The new species, Milnesium beasleyi sp. nov., differs from other known species of the gran-ulatum group by having sparsely distributed cuticular depressions (pseudopores) that do not form an apparent reticulum.In addition to the unique cuticular sculpturing, the new species differs from other congeners also by some morphometriccharacters. Macrobiotus reinhardti Michalczyk & Kaczmarek, 2003 is a new record for Turkey and it is also the first re-cord of this species outside its type locality on Cyprus. The new records raise the number of known Turkish water bearspecies to 50. In this paper, we provide a full list of the known Turkish tardigrade species with their localities. Moreover, we present some zoogeographical and taxonomic issues concerning Turkish tardigrades.